2018
DOI: 10.1002/anie.201811711
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Coordination Landscape of a Digold(I) U‐Shaped Metalloligand

Abstract: A U‐shaped di‐gold metallotweezer with two pyrene‐imidazolylidene edges and a xanthenyl‐bis‐alkynyl connector was prepared. This metallotweezer acts as metalloligand in the presence of Cu+, Tl+, or Ag+, showing three clearly distinct coordination patterns depending on the cation used. The coordination to Cu+ leads to a complex in which the metalloligand is coordinated in a pincer form. The reaction with Tl+ affords a complex in which the ligand is acting as a ϰ2‐(trans)‐chelate ligand. The reaction with Ag+ le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…The results that we observed are summarized in Scheme . The addition of [Cu(CH 3 CN) 4 ]BF 4 or TlPF 6 invariably generated the formation of the self‐aggregated complexes 4 and 5 , which could be obtained quasi‐quantitatively, and were unambiguously identified according to our previously published data . These species consist of the encapsulation of the metal cations (Cu + or Tl + ), in the cavity formed by the self‐aggregated structure of 2 ( 4 can be seen as Tl + @ 2 2 , and 5 as Cu + @ 2 2 ).…”
Section: Methodssupporting
confidence: 66%
“…The results that we observed are summarized in Scheme . The addition of [Cu(CH 3 CN) 4 ]BF 4 or TlPF 6 invariably generated the formation of the self‐aggregated complexes 4 and 5 , which could be obtained quasi‐quantitatively, and were unambiguously identified according to our previously published data . These species consist of the encapsulation of the metal cations (Cu + or Tl + ), in the cavity formed by the self‐aggregated structure of 2 ( 4 can be seen as Tl + @ 2 2 , and 5 as Cu + @ 2 2 ).…”
Section: Methodssupporting
confidence: 66%
“…In particular, we observed that the tweezer with the anthracenyl spacer A had a great tendency to dimerize forming non-covalently bound self-aggregated duplex complexes [9,10,12]. In contrast, the complex connected with the xanthenyl spacer B served as a metalloligand for metals such as Cu + , Ag + , and Tl + [11]. The complex with the carbazolyl spacer C was able to encapsulate planar aromatic guests by approaching its two polyaromatic arms, and thus showed an interesting example of a guest-induced-fit conformational arrangement [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, we reported a series of metallotweezers based on the use of two pyrene-bis-imidazolylidene-gold(I) arms bound with four different bis-alkynyl spacers (Scheme 1) [9][10][11][12][13][14][15]. These tweezers benefit from the tendency of Au(I) complexes to show linear geometry, and from the ability of the pyrene moieties to establish π-π-stacking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the anthracenyl‐linked complex 1 showed a great tendency to self‐aggregate in non‐polar solvents and in the presence of cations such as Cu + , Ag + and Tl + [9] . The xanthenyl‐linked complex 2 showed interesting coordinating abilities that were highly dependent on the type of metal used [9b,10] . Finally, the carbazolyl‐linked complex 3 , was able to encapsulate planar polycyclic aromatic hydrocarbons (PAHs), displaying larger associating constants for those planar guests functionalized with groups able to hydrogen bond with the NH group of the carbazolyl spacer [11] .…”
Section: Introductionmentioning
confidence: 99%
“…[9] The xanthenyl‐linked complex 2 showed interesting coordinating abilities that were highly dependent on the type of metal used. [ 9b , 10 ] Finally, the carbazolyl‐linked complex 3 , was able to encapsulate planar polycyclic aromatic hydrocarbons (PAHs), displaying larger associating constants for those planar guests functionalized with groups able to hydrogen bond with the NH group of the carbazolyl spacer. [11] Noteworthy, all our host‐guest chemistry studies with 3 were performed using electron‐donor planar guests, thus the association constants that we found were rather low.…”
Section: Introductionmentioning
confidence: 99%